Karakteristik Fisikokimia Tepung Pisang Tongka Langit (Musa troglodytarum L.) Pregelatinisasi dengan Variasi Penambahan Air - Gilian Tetelepta; La Sarman; Gelora H Augustyn; Febby J Polnaya (Universitas Pattimura, 2025)
This study aimed to characterize the physicochemical properties of pregelatinized tongka langit banana flour with varying levels of water addition. A completely randomized design with a single factor of water addition was employed, consisting of four treatment levels (0, 15, 20, and 25%) and three replications. The results indicated that tongka langit banana flour, both without and with pregelatinization treatment, exhibited water content ranging from 5.38 to 12.90%, ash content from 3.88 to 17.96%, water absorption capacity from 1.54 to 1.83%, solubility from 0.13 to 0.20%, swelling power from 0.14 to 0.17 g/g, and amylose content from 15.23 to 23.33%. Pregelatinization treatment enhanced water absorption capacity, amylose content, swelling power, and solubility, while reducing the water and ash content of tongka langit banana flour.